Expression of MACC1 and c-Met in human gastric cancer and its clinical significance - Guo, Tiankang (BioMed Central, 2013)
BACKGROUND: Recent studies have suggested that the metastasis-associated colon cancer1 (MACC1) gene can promote tumor proliferation, invasion and metastasis through an upregulation of c-Met expression. However, its role in gastric cancer is controversial. Our study investigated expression of MACC1 and c-Met in gastric cancer, as well as correlated this with clinicopathological parameters. METHODS: Expressions of MACC1 and c-Met protein in a sample of 98 gastric carcinoma and adjacent nontumorous tissues were detected by immunohistochemistry. Their relationships and correlations with clinicopathological features were analyzed. RESULTS: The positive rates of MACC1 and c-Met protein in primary tumors were 61.22% and 59.18%, respectively. A significant correlation was found between expression of MACC1 and c-Met (P<0.05). Expression of the MACC1 protein in gastric cancer tissue was correlated with lymph node metastasis (χ(2) = 10.555,P = 0.001), peritoneal metastasis (χ(2) = 5.694, P = 0.017), and hepatic metastasis (χ(2) = 4.540,P = 0.033), but not with age, gender, tumor size, location, clinical stage or the distant metastases (P>0.05). CONCLUSION: The positive rate of MACC1 protein expression was related to the protein expression of c-Met. Both had a correlation with the presence of peritoneal metastasis, lymph node metastasis and hepatic metastasis, all of which contribute to a poor prognosis for gastric cancer patients.